O pojęciu idiostylu translatorskiego (na materiale utworu Krzysztofa Bartnickiego pt. „Garutko sobotniej ropy czyli Jana Kochanowskiego «Pieśni świętojańskiej o Sobótce» (1586) spopolszczenie w sześć par prawie tekstów”) - Sławek, Ewa (Idiolekty, 2025)
Using Krzysztof Bartnicki’s work "Garutko sobotniej ropy, or Jan Kochanowski’s <<Pieśń świętojańska o Sobótce>> (1586) Polonized into Six Pairs of Near-Texts" as a foundation, this paper proposes to extend the scope of idiolectological research to include the linguistic practices of authors whose literary output is inherently shaped by their experiences as translators. The study argues for the introduction of the term translational idiolect to describe the unique language of such writers. The juxtaposition of Bartnicki’s text with Kochanowski’s original 16th-century work demonstrates that Bartnicki’s translational idiolect is marked by its ability to merge elements from multiple languages and cultures, including their dialects and sociolects. Furthermore, this idiolect exhibits a remarkable capacity for creative deformation and innovative transformations. The hallmark features of Bartnicki’s translational idiolect include linguistic hybrids and neologisms.